Interview with María Antonia Casanova Rodríguez, Education Inspector, University Lecturer, and Expert in Educational Assessment and Inclusion - Faci Lucia, Fernando M. (Avances en Supervisión Educativa, 2026)
Interview with María Antonia Casanova Rodríguez, Education Inspector, University Lecturer, and Expert in Educational Assessment and Inclusion.